Neodualism in the Italian business firms: Training, organizational capabilities and productivity distributions - Giovanni Dosi; Dario Guarascio; Andrea Ricci; Maria Enrica Virgilito (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2018)
What has been the dynamics of productivity in the Italian business firms in the aftermath of the crisis? And what has been the impact of training efforts upon such dynamics? In this work we address these questions exploring a unique Italian microlevel dataset which links information on the amount and the nature of training and the balance-sheet data. First, we document what we call a neo-dualist tendency with a leader-laggard dynamics entailing a widening support of the productivity distributions. Second, we analyze the relationship between productivities and training intensities by means of quantile regression analysis, also controlling for additive fixed effects by means of Canay (2011) technique. There is indeed some relationship in the whole sample which however gets weaker when disaggregating by sector and by size. Moreover, hardly any dynamic relationship appears, either between initial training intensities and subsequent productivity changes, nor between changes in both variables. Our results do not imply of course that training is not important, but that its effectiveness must be shaped by other firm-specific characteristics, plausibly associated with idiosyncratic organizational capabilities.
Keywords: M53; O12; D22; 330; productivity; firm-level heterogeneity; training; organizational capabilities